Geographic information systems for occupational cancer surveillance: a scoping review - Sanchez, Diana Carolina; Talero, Lorena Lisbeth; Mejia-Duarte, Jose Ferney; Mendoza-Monsalve, Alejandra; Licht-Ardila, Maricel; Hurtado-Ortiz, Alexandra (Revista Cuidarte, 2025)
Highlights • Geographic Information Systems (GIS) in oncology are key tools for analysis, surveillance, and data extraction. • Oncology publication topics follow the global cancer prevalence pattern, with increasing interest in occupational cancer. • The use of GIS has allowed for addressing the relationship between pollutant exposure and the increased incidence of cancer in various regions. • Through GIS, a better understanding of disparities in healthcare access has been achieved, enabling the optimization of resources. Introduction: Geographic Information Systems (GIS) are key tools for managing spatial data and understanding the determinants of occupational cancer. Objective: To evaluate the applications, advantages, and limitations of GIS in the surveillance of occupational cancer. Materials and Methods: A systematic scoping review was conducted using PubMed, Embase, Scopus, and Bireme databases, following the Population, Context, and Concept (PCC) framework outlined in the Joanna Briggs Institute (JBI) methodological guidelines and the PRISMA ScR. A semi-automated process supported by Rayyan® software was employed for study selection. The variables identified were transferred to a spreadsheet for qualitative analysis and synthesis. Results: A total of 55 articles were included, addressing various cancer types and exposure to industrial emissions and potentially carcinogenic pollutants. The most commonly used GIS, spatial analysis methodologies, and the main advantages and limitations of their use were identified in monitoring morbidity and mortality, equity, timeliness, coverage, and access to health services, as well as in modeling environmental agents. Discussion: GIS advance cancer research by integrating and analyzing diverse datasets, mapping cases, and identifying risk factors. Challenges include data accuracy, incomplete records, and omission of socioeconomic variables. Despite limitations, GIS support cancer surveillance, occupational health policies, and prevention plans. Conclusion: GIS are valuable tools for cancer surveillance, as they improve understanding of the geographic patterns of exposure and associated variables, providing critical insights for public policy formulation, healthcare planning, and preventive strategies. How to cite this article: Sanchez Diana Carolina, Talero Lorena Lisbeth, Mejia-Duarte Jose Ferney, Mendoza-Monsalve Alejandra, Licht-Ardila Maricel, Hurtado-Ortiz Alexandra. Geographic information systems for occupational cancer surveillance: a scoping review. Revista Cuidarte. 2025;16(3):e4747. https://doi.org/10.15649/cuidarte.4747